2003
DOI: 10.1097/01.ta.0000037876.37236.d6
|View full text |Cite
|
Sign up to set email alerts
|

Harbingers of Poor Outcome the Day after Severe Brain Injury: Hypothermia, Hypoxia, and Hypoperfusion

Abstract: Our early management of head-injured patients stresses avoidance and correction of SBIFs at all costs. Nonetheless, SBIFs occur frequently in the first 24 hours after traumatic brain injury. Six of the 11 factors studied are associated with significantly worse outcomes. Hypotension and hypothermia are independently related to mortality. Because these SBIFs are potentially preventable, protocols could be developed to decrease their frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
152
4
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(169 citation statements)
references
References 32 publications
3
152
4
7
Order By: Relevance
“…While hypothermia on admission is common in trauma patients with more severe injuries and poor prognoses (Little and Stoner, 1981;Little, 1985;Steinemann et al, 1990;Jeremitsky et al, 2003), it is currently unclear if hypothermia contributes to poor outcome or is simply correlative (Steinemann et al, 1990). We did not observe significant differences in any physiologic or neurologic outcome measures between the brain-injured animals that were hypothermic for 12 to 24 hours after injury and those that developed PTH.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…While hypothermia on admission is common in trauma patients with more severe injuries and poor prognoses (Little and Stoner, 1981;Little, 1985;Steinemann et al, 1990;Jeremitsky et al, 2003), it is currently unclear if hypothermia contributes to poor outcome or is simply correlative (Steinemann et al, 1990). We did not observe significant differences in any physiologic or neurologic outcome measures between the brain-injured animals that were hypothermic for 12 to 24 hours after injury and those that developed PTH.…”
Section: Discussionmentioning
confidence: 52%
“…The brain-injured patient often has multiple injuries, including fractures, hemorrhage, etc., that may present with hypotension and hypoxia as well as hypothermia (Statler et al, 2001). Although these factors have been shown to relate to poorer outcome after TBI (Jeremitsky et al, 2003), isolated hypothermia may or may not be causative of poor outcome. Because it has also been suggested that therapeutic postinjury hypothermia is neuroprotective (Clifton et al, 1991;Dietrich 1992;Marion et al, 1997;Kinoshita et al, 2002a, b), the findings of this study provide additional information to aid in the design of future preclinical neuroprotection studies.…”
Section: Discussionmentioning
confidence: 99%
“…Hypotension has been related with increased mortality, and hypoxia, hypocapnia, increased ICP, and acidosis were associated with poor outcome. 63 From the two prospective clinical trials of magnesium in TBI reported by Temkin et al 1 and Dhandapani et al, 2 it is evident that in clinical trials on brain injuries a study design with more stringent inclusion-exclusion criteria need to be considered, to account for secondary brain insults and parameters likely to adversely affect outcome, such as severity of head injury, multiorgan injury, age limits, renal function, pre-existing health conditions, concomitant medication, use of tobacco and alcohol, and history of substance abuse.…”
Section: Secondary Insults In Traumatic Brain Injurymentioning
confidence: 99%
“…The optimal resuscitation constitutes the first step in the optimal treatment of the brain trauma patient, in virtue of the acknowledged deleterious role of secondary insults such as hypotension and hypoxia [125,126]. Maintaining SatP at a level >94%, the systolic blood pressure above 90 mm Hg, the mean arterial blood pressure above 70 mm Hg, and the PaCO 2 around 35 mm Hg seem reasonable goals [124].…”
Section: Initial Neurologic Evaluation Of the Trauma Patientmentioning
confidence: 99%